Modern methods and technologies of time management - Zhukovska, A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
This research focuses on the study of many methods, techniques, technologies, tools, rules, and principles of modern time management. The aim of the study is to develop their generalized classification based on different criteria, and to assess their potential usefulness for different types of people and organizations. The article proves that world practice has many different methods, techniques, techniques, technologies, tools, techniques and principles of time management. All of them are actively used in practice. In the article, all methods and technologies of time management are offered to be divided on the basis of three criteria: depending on a way of the organization (paper, digital and mixed); depending on the origin (classical and derivative); depending on the principles underlying them (methods of time distribution and methods of its control, methods of distribution and differentiation of tasks, methods of productivity control, methods of information processing and storage and methods of combating procrastination). This classification allows users to navigate in a variety of time management methods and choose those that will take into account their individual needs. They are not mutually exclusive, and if desired, they can be used in various combinations to meet individual needs. The article emphasizes that in the age of digitalization there are more and more flexible, fast and convenient digital time management systems. With the expansion of Internet access, most online services are moving to the form of web-services, which with the help of a web-browser allow you to use them from any electronic device (computer, tablet or smartphone) anywhere in the world. Therefore, we consider promising for further research a detailed study of digital methods of time management, analysis of their main functions, identifying the advantages and disadvantages that they give users.